Ferrocene‐Peptide Conjugate for the Detection and Quantification of Ascorbic Acid - Tsuimy Shao; Junyan Wang; Dr. Meissam Noroozifar; Prof. Dr. Heinz‐Bernhard Kraatz (ChemElectroChem, 2023)
Abstract Ferrocene (Fc) is a widely used metallocene, with well‐characterized redox behaviour that is vastly used in a variety of applications. Ferrocene‐coupling to peptides renders the resulting bioorganometallic peptide conjugate redox active and sensitive to changes in the chemical environment. The disulfide‐linked ferrocene peptide conjugate (FcCO‐Phe‐Cys‐OH)2 was synthesized and characterized by NMR, MS, and FT‐IR spectroscopies and then exploited for the detection of ascorbic acid. Here we demonstrate that the Cu(II) complex of this peptide conjugate allows the detection of ascorbic acid with a limit of detection of 0.02 μM with a linear range of 0.1–25 μM. This is the first report of the use of a peptide metal complex for direct modification of a glass carbon electrode and its application for ascorbic acid detection and quantification, including in commercial beverages. The modified GCE exhibited excellent selectivity, stability, and sensitivity.